THE APPLICATION OF SCRAMBLE GAMES TO IMPROVE STUDENTS’ WRITING SKILLS IN ENGLISH LANGUAGE LEARNING - Khoiriya, Sefyathul (Antis-Publisher, 2024)
This study aims to explore the effectiveness of using scramble games as a teaching method to improve students’ writing skills. The research is based on the low English language proficiency, particularly in writing, among Indonesian students. Scramble games, which involve arranging wors or sentences randomly, were chosen as a teaching mehod to make the writing learning spocess more engaging and interactive. The results of the study indicate that this method can help students better understand vocabulary and sentence structure as wellas enhance critical and collaborative thinking skills.